RELEVANSI KONSEPTUAL MODEL HADITS PENDIDIKAN KARAKTER DALAM KELUARGA PERSPEKTIF KITAB ADAB AL-MUFRAD DAN TARBIYAH AL-AULAD FI AL-ISLAM TERHADAP KONTEKS KEKINIAN - Nailul Ghufron Aziz (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2019)
The importance of character education as the direction and estuary of national education, bring the consequences of education to make the nation‟s character strong positive (sturdy, unshakable in the holding the good values which sourced of religion, culture-tradition or the state of philosophy). However the issues about the character or moral that happen at the present time, far more and complex compared with education character issues that happened in the previous time. There are some strategies that has done to give character education for child that started from family environment its self, because the child character formed from family education. The character issues that more complexs make the person aware the importance of review the theory of Prophet Muhammad SAW from hadis (traditional collection of stories relating words or deeds of Muhammad the chief source of guidance for understanding religious questions) to give the appropriate education character for child. Here the writer will present The Relevance of Family Education Character Perspective Adab al-Mufrad and Tarbiyah al-Aulad fi al-Islam Book toward the context of Education Character that happen at the present time.